THE EFFECT OF IMPULSE ON A FALLING ROD-CHAIN - Shim, Gina (MATTER: International Journal of Science and Technology, 2017)
When a chain with a tilted rod collides with the horizontal surface, the chain falls faster than when it free falls. If one moving object collides with a rigid object, then the velocity of the moving object is supposed to become slower. However, in the case of this phenomenon, the impulse from the colliding section determines the acceleration of the falling chain. This system is mostly related to change in momentum, so the calculation of the change in velocity throughout the phenomenon was done with linear momentum and angular momentum theories. After making a theoretical equation, the calculated acceleration was compared with experimental acceleration.